Arena: A Critical Conceptual Framework of Top Management Selection. (February 2014) - Vinkenburg, Claartje J.; Jansen, Paul G. W.; Dries, Nicky; Pepermans, Roland
While the selection of top managers is vital to the performance and survival of organizations, the process by which these managers are selected remains uncharted territory. In this conceptual article, we propose that both structural conditions of and the selection process for top management positions are different from those at lower organizational levels. We build on the existing literature on succession, tournament models, and promotion systems to characterize top management selection. The main situational component of this characterization is that of relative versus absolute selection, which leads us to adopt the "arena" as a metaphor and critical framework for top management selection. Finally, we argue that due to certain cognitive features, the arena is an efficient but not necessarily effective selection process, which may contribute to side effects and negative outcomes for organizations. We conclude by setting the agenda for further research on top management selection.